PENGARUH PERTUMBUHAN PENJUALAN TERHADAP PROFITAILITAS PADA PT.GUDANG GARAM TBK - Nurul Huda; Purnama Putri Sya’dah (INVOICE : JURNAL ILMU AKUNTANSI, 2020)
Purpose of this research is to know the influence of sales growth to profitability in PT. Gudang Garam Tbk. The population of this research is the financial report of sales growth and net profit in PT. Gudang Garam TBK, for 10 years IE 2009-2018. The sample will be the financial report of sales growth and net profit in PT. Gudang Garam, for 5 years which is 2014 – 2018. This is an associative research with sampling techniques that is purposive sampling. The test results showed that there was no significant influence between sales growth on profitability at PT Gudang Garam Tbk. With a value of R2 of 16.1%.